Application Of Factorial Design To Optimize Lubricant Concentration And Granule Mixing Time In The Formulation Of Sour Star Fruit (Averrhoa bilimbi L) Ethanolic Extract Tablet - Setiyadi, Gunawan; Putri, Yola Veranita (Pharmacon: Jurnal Farmasi Indonesia, 2024)
The use of lubricant in tablet compaction can reduce both intergranular and granule to die-wall friction that in turen improve granule flow properties and reduce adhesion of granule mass to the die wall. However, the concentration and method of adding lubricants into granule mass has also been known to influence the physical properties of tablets, such as hardness, friability, disintegration time and dissolution. This study aimed to apply 2-factor-2-level-factorial (22) design to determine the effect of lubricant concentration in granule mass (factor A) and the granule mixing time (factor B) on the physical properties of granules and tablets of starfruit leaves (Averrhoa bilimbi L.) ethanolic extract and to obtain the optimum setting of both factors that results in responses that satisfy most of the predefined criteria. The factorial design was set as follows: (l) = 2.5%, 5 minutes, a = 5%, 5 minutes, b = 2.5%, 15 minutes, and ab = 5%, 15 minutes. The lubricant used was a mixture of magnesium stearate and talc in a ratio of 1:9. Experimental design and optimization were carried out using Design Expert 13.0 software with granule flowability, angle of repose, and compressibility, as well as tablet weight uniformity (%RSD), hardness, friability, and disintegration time as responses. Optimum results were obtained with 2.5% lubricant and 5 minutes factor combination. The verification test to the optimum parameters showed that the granule flowability, angle of repose, tablet hardness and tablet friability are within the prediction interval range (PI 95%).